2019
DOI: 10.1055/a-0831-2522
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surveillance after surgical or endoscopic resection for colorectal cancer: European Society of Gastrointestinal Endoscopy (ESGE) and European Society of Digestive Oncology (ESDO) Guideline

Abstract: Main Recommendations 1 We recommend post-surgery endoscopic surveillance for CRC patients after intent-to-cure surgery and appropriate oncological treatment for both local and distant disease.Strong recommendation, low quality evidence. 2 We recommend a high quality perioperative colonoscopy before surgery for CRC or within 6 months following surgery.Strong recommendation, low quality evidence. 3 We recommend performing surveillance colonoscopy 1 year after CRC surgery.Strong reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 132 publications
(129 reference statements)
0
60
0
3
Order By: Relevance
“…Three studies presented evidence per age group relative to the younger age group. Martinez et al 12 reported statistically significant increased risks for AN across three age groups (61–71; 80+years) compared with the younger age group (50–59 years), with incidence of AA at first surveillance as 12.2%, 14.5%, and 17.7%, respectively. Furthermore, Martinez et al also presented evidence on the younger than 40 age group, and the 40–49 age group relative to the 50–59 age group.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Three studies presented evidence per age group relative to the younger age group. Martinez et al 12 reported statistically significant increased risks for AN across three age groups (61–71; 80+years) compared with the younger age group (50–59 years), with incidence of AA at first surveillance as 12.2%, 14.5%, and 17.7%, respectively. Furthermore, Martinez et al also presented evidence on the younger than 40 age group, and the 40–49 age group relative to the 50–59 age group.…”
Section: Resultsmentioning
confidence: 98%
“…The risk of metachronous cancer development is highest in the first 3 years after diagnosis of CRC 66 70. This increased risk is particularly common in older studies or in those where perioperative colonoscopy was not systematically performed 70.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large retrospective cohort study from the UK evaluating the effectiveness of post-polypectomy colonoscopy surveillance on incident colorectal cancer, Cross et al reported that, compared with the general population, CRC incidence without surveillance was similar among low-risk and intermediate-risk groups, but significantly higher in the high-risk group. However, a possible exception is the need for early colonoscopy surveillance following complex polyp resection (for example, endoscopic mucosal resection or endoscopic submucosal dissection) or following endoscopic management of early gastric cancer because these patients have been shown to be at high-risk for residual or recurrent disease 9,10 . Delays for endoscopic surveillance are now common owing to endoscopy units temporarily suspending such procedures, a lack of endoscopy personnel to perform these procedures as many have been assigned to other medical wards to care for patients with COVID-19 or are sick or isolating themselves, or because patients decide to stay away from hospitals.…”
mentioning
confidence: 99%